Analysis of TGF-β1 and p53 Expression in The Blood of Stroke Patient - Wulandari, Endah; Hapsari, Rr Ayu Fitri; Birowo, Hendro (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Stroke is a dysfunction of brain tissue due to deficiency of blood circulation to the brain. This causes disruption of blood supply and oxygen in the brain. Stroke not only needs to be handled in post-event, but also needs to be understood the cause of the occurrence by molecular, so that the drug will be right on target. Inflammation is associated as a secondary injury mechanism in the case of stroke. Dendritic cells which secreted TGF-β, it functions to regulate proliferation, differentiation and activate other cytokines in cell growth. It is strongly suspected that Transforming Growth Factor-β1 (TGF-ß1) is a determinant of cytokines in nerve tissue recovery. Neural cell malfunction or nerve cell death is thought to be the role of p53 protein. Methods: The design of this research is observation. This research measures TGF and p53 expression in the stages of mRNA (RT-PCR) and protein (ELISA) in the blood of stroke patients. Results: The expression of TGF- β1 and p53 mRNA in the blood of stroke patients is higher (50 and 45 times; Unpaired p <0.01) than normal. TGF- β and p53 protein levels in the blood of stroke patients are higher than normal (20,607 vs 1,895 pg/mLx10; 44,418 vs 11.63 pg/ mL; Unpaired 0 <0.01). The correlation of both TGF- β1 and p53 shows a strong positive. Discussion: The expression of increased TGF- β1 and p53 In the blood of stroke patients. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 35-40